Finely Formed, Kinetically Modulated Wrinkle Structures in UV‐Crosslinkable Liquid Prepolymers. Issue 22 (8th September 2015) - Park, Seung Koo; Kwark, Young‐Je; Moon, Jaehyun; Joo, Chul Woong; Yu, Byounggon; Lee, Jeong‐Ik
Abstract : Special characteristics of wrinkles such as a scattering source and a high surface area are finding use in high‐tech applications. UV‐crosslinkable prepolymers are occasionally used for fabricating wrinkled films. Wavelength of the wrinkles formed from the prepolymers is several tens and hundreds of micrometers. Here, a UV‐crosslinkable liquid prepolymer is synthesized to spontaneously form wrinkle structures in the order of several micrometers. Double layers with a very thin hard skin and a soft and contractible foundation are formed at the same time, by ensuring that all the absorbance wavelengths of the photoinitiator are shorter than the minimum wavelength at which the prepolymer is transparent. The rate of photo‐crosslinking reaction, R p, is also found to affect the thickness of the skin and foundation layers at the early UV‐curing stage. The first‐order apparent rate constant, k app, is between ≈0.20 and ≈0.69 s −1 for the wrinkle formation. This wrinkle structures can be simply modulated by changing R p . Abstract : Wrinkle structures with a scale of several micrometers can be achieved using a UV‐crosslinkable liquid prepolymer and modulated by altering the rate of photo‐crosslinking reaction ( R p ). The R p as well as the relationship between absorbance of a photoinitiator and a prepolymer is found to affect the thickness of the hard skin and soft foundation layers at the early UV‐curing stage.